Reimagining religious education: integrating ethnographic and anthropological perspectives - Marshall, Heather (British Journal of religious education, 2024)
The Ofsted Subject report series: Religious Education (2024) and the CoRE report (2018) critically evaluate the shortcomings of the current Religious Education (RE) curriculum in UK schools, highlighting a lack of depth and consistency that inadequately prepares students for a diverse and complex world. This paper proposes the integration of ethnographic and anthropological methods into the RE curriculum as a transformative solution to enhance pedagogical effectiveness and deepen students’ understanding of religious practices. By employing these methods, the curriculum can offer a more immersive, reflective, and comprehensive educational experience, aligning RE more closely with the realities of a multicultural and multi-faith society. This integration not only enriches students’ learning but also fosters greater empathy and a nuanced appreciation of religious diversity, addressing the educational challenges highlighted by Ofsted and CoRE.